INNOVATIVE DESIGN AND DEVELOPMENT OF A SMART SOLAR- POWERED THERMOELECTRIC MEDICAL BOX FOR EMERGENCY AND REMOTE HEALTHCARE - Aftab Ahmed Soomro; Asmatullah; Komal Tanveer; Abdul Hameed; Sumbal Ayyaz; Adv.Engr.Samee Ullah Joyia; Fakhar Anjam; Ali Mujtaba Durrani; Basit Ahmad (Spectrum of Engineering Sciences, 2025)
The storage and transportation of medical supplies, particularly in remote or emergency situations, present significant challenges, especially when electricity is limited or unavailable. This paper presents the design and development of a smart, solar-powered thermoelectric medical box that addresses these challenges. The box utilizes the Peltier effect for thermoelectric cooling, ensuring that medications and other temperature-sensitive supplies remain safe from heat and direct sunlight without the need for harmful refrigerants or conventional refrigeration systems. The system is powered entirely by solar energy, making it ideal for use in off-grid areas and regions where electricity access is unreliable. It features an efficient energy management system that allows the box to operate for up to 10 days on a single charge from its integrated solar panel and battery bank, making it suitable for long-term deployment in disaster zones, war zones, or remote healthcare settings. In addition to its cooling capabilities, the box is designed to be compact, rugged, and easy to transport, ensuring that it can withstand harsh environmental conditions, such as extreme heat, humidity, or rough terrain. The project aims to provide a sustainable and reliable solution for emergency medical storage and delivery, ultimately improving healthcare access in challenging environments. This design is particularly significant in areas where reliable refrigeration is unavailable, offering a practical tool to support global health initiatives.